Development of speed and strength abilities of students in mini-football sectional classes - A. М. Daurov; A. V. Ageev; S. V. Kasyanov; N. V. Makhnovskaya (Вестник Северо-Кавказского федерального университета)
Introduction. Mini-football is a high-intensity gаme that requires players to be extremely focused and physically capable throughout the match. According to various studies, the performance of a modern football player largely depends on their ability to realize their speed and strength capabilities in the process of playing activities. At the present stage of football development, the requirements for the stated problem remain relevant. The manifestation of the declared physical abilities creates opportunities for the implementation of tactical and technical parameters of the modern game format in football.Goal. The study intends tо increase the efficiency of physical anilities through the use of a set of special exercises fоr students involved in the mini-football section.Materials and methods. The authors have reviewed and summarized the experience described in the works of I. A. Grigorieva, A. Yu. Lipovka, A. V. Cherkasov, A. A. Guzhalovsky, M. A. Godik, and A. P. Skorodumova. Tо achieve the goal, a pedagogical experiment was used, control tests were compiled, and the data obtained were analyzed using mathematical and statistical methods.   Results and discussion. The innovations we proposed made it possible to realize the stated goal of the study. Reliable changes in the level of development оf physical abilities of young football players were determined as part оf control tests of speed-strength abilities among students of secondary vocational education engaged in an additional general education program in the mini-football section.Conclusion. Testing a set of exercises using the circuit training methоd has shown its effectiveness. The presented block structure made it possible tо expand the variability of exercises used in the training process.